2020
DOI: 10.1002/mrc.4987
|View full text |Cite
|
Sign up to set email alerts
|

Identifying aspirin polymorphs from combined DFT‐based crystal structure prediction and solid‐state NMR

Abstract: A combined experimental and computational approach was used to distinguish between different polymorphs of the pharmaceutical drug aspirin. This method involves the use of ab initio random structure searching (AIRSS), a density functional theory (DFT)-based crystal structure prediction method for the high-accuracy prediction of polymorphic structures, with DFT calculations of nuclear magnetic resonance (NMR) parameters and solid-state NMR experiments at natural abundance. AIRSS was used to predict the crystal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Crystal structure prediction of L-tyrosine was carried out using the ab initio random structure searching (AIRSS) method, 45,46 which has recently been used successfully for other organic molecular crystals. 93,94 The AIRSS methodology for structure prediction involves two steps: (1) generation of trial structures by "intelligent" random searching, and (2) geometry optimization and energy-ranking of the trial structures using full periodic DFT calculations (PBE-TS).…”
Section: Crystal Structure Predictionmentioning
confidence: 99%
“…Crystal structure prediction of L-tyrosine was carried out using the ab initio random structure searching (AIRSS) method, 45,46 which has recently been used successfully for other organic molecular crystals. 93,94 The AIRSS methodology for structure prediction involves two steps: (1) generation of trial structures by "intelligent" random searching, and (2) geometry optimization and energy-ranking of the trial structures using full periodic DFT calculations (PBE-TS).…”
Section: Crystal Structure Predictionmentioning
confidence: 99%
“…A common method to boost spectral resolution is fast or ultra-fast magic-angle spinning (MAS). In this method, the sample is spun at speeds greater than 40 kHz, with 120 kHz being the maximum frequency currently commercially available. , Fast or ultra-fast MAS has been applied on various APIs to increase 1 H spectral resolution, ,,,, with some using spinning speeds above 100 kHz. ,,, The boost in spectral resolution can facilitate quantitative studies. For instance, Li et al employed an external magnetic field strength ( B o ) of 9.40 T (ν o ( 1 H) = 400 MHz) and showed that 1 H spectral resolution of pioglitazone hydrochloride (PioHCl) salts, an anti-diabetes drug, can be drastically improved at high spinning speeds .…”
Section: Introductionmentioning
confidence: 99%
“…In this method, the sample is spun at speeds greater than 40 kHz, with 120 kHz being the maximum frequency currently commercially available. 36 , 37 Fast or ultra-fast MAS has been applied on various APIs to increase 1 H spectral resolution, 14 , 21 , 30 , 35 , 38 42 with some using spinning speeds above 100 kHz. 38 , 39 , 41 , 42 The boost in spectral resolution can facilitate quantitative studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NMR is a method of choice to study disordered solids. It is a powerful structural probe, and has had many successes in solving chemical structures of active pharmaceutical ingredients (APIs), their polymorphic forms, [2][3][4][5][6][7][8][9] or of amorphous solid dispersions. 10,11 However, sometimes the active ingredient is present in low concentration (<mmol), and the inherently low sensitivity of SSNMR (due to the small difference in nuclear spin populations at ambient temperatures), prevents the acquisition of experiments in a timely manner.…”
Section: Introductionmentioning
confidence: 99%